Higher frequency of peripheral blood follicular regulatory T cells in patients with new onset ankylosing spondylitis. (February 2015) - Shan, Yuxing; Qi, Changlin; Zhao, Jixue; Liu, Yijun; Gao, Hui; Zhao, Ding; Ding, Fupeng; Wang, Jing; Jiang, Yanfang
Summary Follicular helper T (TFH) cells and B cells are linked to the pathogenesis of ankylosing spondylitis (AS). Follicular regulatory T (TFR) cells suppress TFH cell and germinal center B cell numbers in vivo. The role of TFR cells in AS is unknown. The frequency of peripheral blood inducible FOXP3+CXCR5+CD4+TFR cells and CXCR5+CD4+TFH cells were taken from 20 onset AS patients and 10 healthy controls, and were examined by flow cytometry, their disease activity were measured by the Bath Ankylosing Spondylitis Disease Activity Index. The concentrations of serum interleukin (IL)‐21, immunoglobulin G, immunoglobulin A, immunoglobulin M and C‐reactive protein were examined, and the values of erythrocyte sedimentation rate were measured. The frequency of peripheral blood FOXP3+CXCR5+CD4+TFR cells, CXCR5+CD4+TFH cells, the ratio of FOXP3+CXCR5+CD4+TFR/CXCR5+CD4+TFH cells and the concentration of serum IL‐21 in the AS patients were significantly higher than those in the healthy controls (P < 0.0001, P = 0.0027, P < 0.0001, P = 0.0039, respectively). The frequency of FOXP3+CXCR5+CD4+TFR cells and the ratio of FOXP3+CXCR5+CD4+TFR/CXCR5+CD4+TFH cells still significantly rose in those patients after standard treatment (P = 0.0006, P < 0.0001), the concentration of serum IL‐21 decreased after treatment (P = 0.0049), accompanied by significantly minimized disease activities. Furthermore, the TFR cells were negatively correlated with serum immunoglobulin A in those patients before treatment (r = −0.582, P = 0.0071), and the frequency of TFR cells was negatively correlated with that of TFH cells and the concentration of serum IL‐21 after treatment (r = −0.550, P = 0.046; r = −0.581, P = 0.0371). TFR cells might participate in the pathogenesis of AS, and might be responsible for controlling the autoantibodies, the frequency and function of TFH cells to inhibit the development of AS.